Use of Antidiabetic Drugs and Glycemic Control with Life Style Management in Type II DM-A Cross-Sectional Study General Practice in Odisha - Mohapatra, Prabhudatta; Kar, Durga Madhab; Rath, Karmajeet; Pal, Abhisek (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background Our objective is to describe the patterns of prescribing drug combinations and lifestyle modification in which therapy focuses on SGLT2 and DPP4 inhibitors and dose variation according to the blood glucose level and the effective therapy in patients with T2DM. Materials and Methods Using both prescription and questionnaire analysis, a cross-sectional study conducted in Odisha, including 100 diabetic subjects, is considered to evaluate effective combination therapy by comparing different glycemic indexes with Lifestyle modification. Results and Discussion Age and duration of detection of diabetes are the factors through which the gender basis comparison is made and comparing the glycemic index according to different consultations, the drug therapy is considered so as to achieve safe and no or less hypoglycemia. Males (52%) constituted more than female (48%) respondents. The presence of T2DM was responded by 57%, whereas 68% suggest there is no permanent cure for T2DM. The lifestyle changes with medicine, in control of T2DM has been reported by 59% of respondents. There is a significant change (p≤0.005) in FBS and PPBS levels as compared from 1st visit to 5th visit with the effective combination of Metformin and teneligliptin. Conclusion DPP4 inhibitor and SGLT 2 inhibitor are the newer antidiabetic drugs used as add-on therapy to minimize different risk factors and enhance the quality of life. It is essential to consider diabetes education to improve knowledge of the risk factors associated with type 2 diabetes.
Keywords: Diabetes; Drug; Drug Utilisation Pattern; DPP4i; SGLT2i